Macroprudential Banking Regulation: Does One Size Fit All? - Doris Neuberger; Roger Rissi (Journal of Banking and Financial Economics, 2014)
The macroprudential regulatory framework of Basel III imposes the same minimum capital and liquidity requirements on all banks around the world to ensure global competitiveness of banks. Using an agent-based model of the fi nancial system, we fi nd that this is not a robust framework to achieve (inter)national fi nancial stability, because effi cient regulation has to embrace the economic structure and behaviour of fi nancial market participants, which differ from country to country. Market-based fi nancial systems do not profi t from capital and liquidity regulations, but from a ban on proprietary trading (Volcker rule). In homogeneous or bank-based fi nancial systems, the most effective regulatory policy to ensure fi nancial stability depends on the stability measure used. Irrespective of fi nancial system architecture, direct restrictions of banks’ investment portfolios are more effective than indirect restrictions through capital, leverage and liquidity regulations. Applying the model to the Swiss fi nancial system, we fi nd that increasing regulatory complexity excessively has destabilizing effects. These results highlight for the fi rst time a necessary change in the regulatory paradigm to ensure the effectiveness and effi ciency of fi nancial regulations with regards to fostering the resilience of the fi nancial system.